The Relationship Between Frequency of Injuries and Workplace Environment in Korea: Focus on Shift Work and Workplace Environmental Factors - Jongwoo Kim (Elsevier, 2018)
Background: The purpose of this study was to investigate the effect of shift work on occupational safety in various industrial sectors. The study analyzes the effects of shift work on the health of workers by considering factors such as the workplace environment and welfare. Methods: Focusing on the 4th Korean Working Conditions Survey, this study used an ordinary least-square multiple regression analysis. The dependent variable was the annual frequency of injuries reported by workers. Independent variables were categorized as demographic, shift work, workplace environment, and welfare variables. The analysis was conducted on two levels: 1) Shift work and nonshift work groups were compared, and 2) Shift work was compared with fixed and rotating shifts. Results: For the entire group, age, a low level of education, work hours, and daily and dispatch work negatively impacted the frequency of injuries. Shift work was negatively affected by workplace environment and welfare factors. In the shift group, the frequency of injuries was lower than that of regular workers, and the higher the autonomy in the choice of work hours, the lower the frequency of injuries. Furthermore, shift workers in Korea have more extended work hours (49.25 h/week) than other workers (46.34 h/week). Conclusion: Overall, welfare factors such as workplace satisfaction and work-life balance reduced the frequency of injuries. The effect of shift work was limited, but it was confirmed that shift worker autonomy could reduce the frequency of injuries. Keywords: Health, Korean Working Conditions Survey, Occupational safety, Shift work, Workplace environment